2016
DOI: 10.1371/journal.pone.0162495
|View full text |Cite
|
Sign up to set email alerts
|

Improving Diagnostic Accuracy of Dermoscopically Equivocal Pink Cutaneous Lesions with Reflectance Confocal Microscopy in Telemedicine Settings: Double Reader Concordance Evaluation of 316 Cases

Abstract: BackgroundSolitary pink lesions in differential diagnosis with hypopigmented/amelanotic melanoma present a diagnostic challenge in daily practice and are regularly referred for second expert opinion. Reflectance confocal microscopy (RCM) has been shown to improve diagnostic accuracy of dermoscopically equivocal pink lesions. No studies have been performed to evaluate the effect of adding a second expert reader and automatic removal of lesions with discordant management recommendations and its potential effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Previous RCM studies tested performance of single evaluators and reported variable sensitivities and specificities, mainly related to different study settings, study populations and evaluator expertise, but all studies demonstrated a good diagnostic performance in settings of difficult to diagnose lesions [ 5 22 ]. Previous studies include two main types: non-interventional and interventional studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous RCM studies tested performance of single evaluators and reported variable sensitivities and specificities, mainly related to different study settings, study populations and evaluator expertise, but all studies demonstrated a good diagnostic performance in settings of difficult to diagnose lesions [ 5 22 ]. Previous studies include two main types: non-interventional and interventional studies.…”
Section: Discussionmentioning
confidence: 99%
“…These studies mostly evaluated diagnostic performance of RCM alone and differential diagnosis was predominantly based on dermoscopically equivocal lesions [ 5 , 7 10 , 13 22 ]. Reported diagnostic sensitivity was high in all cases (ranging between 84 to 100%) and specificity variable, lower in more difficult study populations such as those containing pink lesions [ 5 , 7 ] and equivocal lesions that presented with architectural changes during sequential digital dermoscopic follow-up [ 8 , 9 ], demonstrating the usefulness and reliability of this methodology for achieving a precise MM diagnosis. The always superior specificity and comparable sensitivity, when compared with dermoscopy alone, suggests the benefit of combined use of these technologies in clinical settings [ 18 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the selected lesions, different criteria were investigated according to RCM features previously outlined in literature . Table shows a brief description of the RCM criteria for non‐melanocytic lesions evaluated in the study.…”
Section: Methodsmentioning
confidence: 99%